Accounting information system : cloud based POS system - Jusoh, Nur Aniza Quantaniah; Fernandez, Dahlia; Abu Seman, Noor Aslinda (Penerbit UTHM, 2020)
Technology has helped businesses in a number of ways that generally centre on doing things bigger, better or faster. Information Technology (IT) deals with the application of computers and telecommunications equipment to store, retrieve, transmit and manipulate data (Wikipedia, n,d). This may also be described as anything that renders data, information, or perceived knowledge in any visual format through any multimedia distribution mechanism (Ghasemi,Shafeiepour, Aslani and Barvayeh, 2011). The role of Information Technology (IT) in business is seen in how it can help a company become more productive, increase performance, save money, improve the customer service and experience, streamline communications and enhance managerial decision-making (Donohue, 2019). ..